The influence of leadership style on learning organization among non-academic staff in UiTM Melaka / Jona Hidayati Qamaruzzaman - Qamaruzzaman, Jona Hidayati (2010)
Many studies have been done on leadership style in learning organization in a business-oriented environment and only a limited amount of research was done in an educational field. The survey instrument for Learning Organization was based on Dimensions of Learning Organization Questionnaire developed by Watkins and Marsick (1993) and survey instrument for Leadership Style was based on Multifactor Leadership Questionnaires developed by Bass and Avolio (1996). This study examined the relationship between the leadership style and learning organization where the population consisted of the non academic staff of UiTM Melaka branch. A total of 155 sets of questionnaires were distributed to UiTM Melaka's non academic staff and 100% were returned and fully completed. The questionnaires were processed using the Statistical Package for Social Science (SPSS) version 16.0 for Windows. Results demonstrated that the transformational leadership highly fostering the learning organization in UiTM Melaka. Study limitations and suggestions for future research were also discussed.